Fuzzy weight neural network in the analysis of concrete specimens and R/C column buckling tests - Jakubek, Magdalena (Computer Assisted Methods in Engineering and Science, 2017)
The paper describes the applications of back propagation neural networks with the ability to process input and output variables expressed as fuzzy numbers. The presentation of an algorithm for finding fuzzy neural network weights is followed by three examples of applications of this technique to the problems of implicit modelling of material and structure behaviour. The following problems are considered: prediction of concrete fatigue failure, high performance concrete strength prediction, and prediction of critical axial load for eccentrically loaded reinforced concrete columns.